The Problem of Prosperity Teaching in Light of Matthew 26:6–13 - Ukoma, Amarichi N.; Nnachi, Ama N.; Eseni, Oji A. (IOSR Journal of Research & Method in Education, 2016)
In African Church the Church is engulfed by prosperity preaching, which is the approach of material procession from God through positive confession induced by Christian preachers. This contemporary religious phenomenon calls for concern among believers. And whereas a critical contrast with Jesus‘ response to Judas Iscariots reaction against His anointing shows that there is something wrong with this idea that sounds like God made a mistake in not creating all fingers equal. This research applied critical exegetic examination of Matt.26:6, related literature, journal and internet materials and found that extreme Prosperity preaching runs contrary to Biblical truth as it places material possession as a yard stick for measuring the kind of God the believer is serving, and it draws a thick line between the relatively poor and the very rich. Consequently this research recommends for a return to the standard gospel that focuses on salvation than prosperity preaching.
free